Production Performances, Meat and Egg Quality, and Serum Biochemical Parameters of Three Native Chicken Genotypes: Laying at Seventh Generation (SAARC Journal of Agriculture, 2023)
The present study was conducted to assess the laying performances and compare the performances of three native chicken genotypes under intensive management. Egg production was recorded up to 280 days. For Kadaknath (K), a total of 500 pedigree hatched day old chicks were identified individually by wing band.  In seventh generation, 26.19%, 10.89% and 18.18% birds of Non-descript Deshi (ND), Hilly (HI) and Naked Neck (NN) had laid egg ranged 80-89%. Chick weight was not affected (p>0.05) by genotype. Fertility of ND, HI and NN was 88.96%, 87.03% and 86.67%, respectively. Significantly (p